Desenvolvimento de suspensões de nanocápsulas para administração sublingual do nifedipino - Osmari, Bárbara Felin (2022)
Nifedipine is a calcium channel blocker drug used in clinical practice in the treatment of cardiovascular diseases, angina and hypertension. However, nifedipine is photo unstable, has a short biological half-life, low aqueous solubility and undergoes intense first pass effect, which compromises its bioavailability when administered orally. In this context, the development of polymeric nanocapsules containing nifedipine may be an interesting alternative to avoid the limitations of this drug viewing the advantages that these systems present, such as the physicochemical protection of actives, increased interaction with tissues or cells, controlled and targeted drug release improved efficacy and reduced adverse effects. Thus, the objective of this work was to develop polymeric nanocapsules containing nifedipine for drug sublingual administration and to evaluate photostability, cyto and genotoxicity, irritation potential, in vitro release profile and ex vivo permeation in porcine sublingual mucosa. Nanocapsules suspensions of Eudragit® RS100 and medium chain triglycerides containing nifedipine and were prepared by the interfacial deposition method of the preformed polymer. The developed formulations showed particle size around 170 nm, polydispersity index below 0.2, positive zeta potential and acid pH. The nifedipine content was 0.98 ± 0.03 mg/mL and encapsulation efficiency of 99.9%. The natural light photodegradation experiment showed that the nanocapsules were able to promote photoprotection nifedipine when compared to the free drug solution. With respect to toxicity assessments the nanocapsules reduced the nifedipine cytotoxicity and showed no genotoxic effects, by the Allium cepa model. Through the HET-CAM test, the formulations were classified as non-irritating. The in vitro release profile in dialysis bags demonstrated that the nanocapsules controlled the release of nifedipine. The ex vivo permeation assay showed that the nanocapsules favored the nifedipine permeation to the receptor compartment. In addition, the nanocapsules provided greater drug retention in the mucosa, which can be attributed to its cationic character. Thus, the development of polymeric nanocapsules suspensions containing nifedipine showed that this system can be a promising platform for sublingual administration of this drug and can lead to the development of other nanobased-dosage forms.